Use of Zeolite ZSM-5 for Loading and Release of 5-Fluorouracil - Ruba A. Al-Thawabeia; Hamdallah A. Hodali (Journal of Chemistry)
Samples of zeolite ZSM-5 have been synthesized in both the sodium form (ZSM-5) and the acid activated form (H-ZSM-5). In addition, each of these two forms was prepared in the two molar SiO2/Al2O3 ratios of 169 and 15. All samples of these ZSM-5 derivatives were characterized by X-ray diffraction (XRD), nitrogen adsorption-desorption isotherms, thermal gravimetric analysis (TGA), X-ray fluorescence (XRF), and scanning electron microscopy (SEM). The samples were successfully loaded with the anticancer drug 5-fluorouracil (5-FU) with loading capacities varying from 22% (for the sodium form having the lower molar SiO2/Al2O3 ratio of 15, ZSM-5-(15)) to 43% (for the corresponding acid form, H-ZSM-5-(15)). Percent release of the drug-loaded ZSM-5 samples into simulated body fluid (SBF) was measured at pH 7.4 and 37°C. The results showed a slight variation in the % release within the range 84–93%, while the first-order rate constant (k) varied from 2.2 h−1 for ZSM-5-(15) to 3.9 h−1 for H-ZSM-5-(15). It was interesting to note that at the higher molar SiO2/Al2O3 ratios of 169, both the sodium form, ZSM-5-(169), and the acid form, H-ZSM-5-(169), exhibit an intermediate efficiency in either % loading (38%) or first-order kinetic release constant (k = 2.9 h−1).